2007
DOI: 10.1177/1088868307301033
|View full text |Cite
|
Sign up to set email alerts
|

How Emotion Shapes Behavior: Feedback, Anticipation, and Reflection, Rather Than Direct Causation

Abstract: Fear causes fleeing and thereby saves lives: this exemplifies a popular and common sense but increasingly untenable view that the direct causation of behavior is the primary function of emotion. Instead, the authors develop a theory of emotion as a feedback system whose influence on behavior is typically indirect. By providing feedback and stimulating retrospective appraisal of actions, conscious emotional states can promote learning and alter guidelines for future behavior. Behavior may also be chosen to purs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
1,117
6
22

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,361 publications
(1,198 citation statements)
references
References 206 publications
53
1,117
6
22
Order By: Relevance
“…Emotional factors include desires, aspirations, fears, and worries that may directly motivate action or serve as a powerful lens through which advantages and disadvantages of alternative actions may be considered. 18 Environmental factors include socioeconomic factors, health system factors, and physical factors, that may facilitate or constrain an individual's behavior. We hypothesized that environmental factors may affect internal cognitive and emotional processes, and also may impact the ability of an individual to successfully carry out behavior change.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Emotional factors include desires, aspirations, fears, and worries that may directly motivate action or serve as a powerful lens through which advantages and disadvantages of alternative actions may be considered. 18 Environmental factors include socioeconomic factors, health system factors, and physical factors, that may facilitate or constrain an individual's behavior. We hypothesized that environmental factors may affect internal cognitive and emotional processes, and also may impact the ability of an individual to successfully carry out behavior change.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…There is much more evidence that emotions influence cognitions than that emotions influence behavior (Schwarz & Clore, 2007). Some ostensible evidence of emotion causing behavior is actually confounded, as shown by further studies with additional controls (for a review, see Baumeister et al, 2007). For example, Bushman, Baumeister, and Phillips (2001) found that anger did not directly cause aggression unless people anticipated that aggressing would make them feel better.…”
Section: Learningmentioning
confidence: 99%
“…We agree that the impulse originates in the automatic system. The role of conscious thought is to reshape (Baumeister, Vohs, DeWall, & Zhang, 2007) and reprogram (Gollwitzer, 1999) those automatic responses through input from culture, as well as to simulate the event mentally before doing it-perhaps also discussing it with real or imagined other people. All this is done to ascertain whether acting out the impulse would be a good idea (to use the common and revealing phrase!…”
Section: Conscious Thought Plays a Supporting Rolementioning
confidence: 99%
“…Roughly speaking, an abstract description of emotions normally consists of a type of processing that analyses a stimulus, and then, through an evaluative process, it signals other mechanisms that control actions and plans (Damasio 2000;Baumeister et al 2007). Emotions are processes that detect opportunities and threats, and the existence or not of a solution, but they barely answer to what the system should do in a given interaction.…”
Section: Aesthetic Emotional Values In Sense-makingmentioning
confidence: 99%